2005
DOI: 10.1016/j.peva.2005.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Scalability of routing methods in ad hoc networks

Abstract: In an ad hoc network each host (node) participates in routing packets. Ad hoc networks based on 802.11 WLAN technology have been the focus of several prior studies. These investigations were mainly based on simulations of scenarios involving up to 100 nodes (usually 50 nodes) and relaxed (too unrealistic) data traffic conditions. Many routing protocols in such setting offer the same performance, and many potential problems stay undetected. At the same time, an ad hoc network may not want (or be able) to limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The performance problems of AODV occur mainly due the high administrative load (see also [26]). One problem of GPSR is that it chooses from the set of neighbors the longest possible hop, which in turn sometimes leads to a poor reception quality and as a consequence to drops of data packets.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance problems of AODV occur mainly due the high administrative load (see also [26]). One problem of GPSR is that it chooses from the set of neighbors the longest possible hop, which in turn sometimes leads to a poor reception quality and as a consequence to drops of data packets.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As the size of a network (number of hosts) grows, various performance metrics start suffering from the increasing administrative load [26,27,21] that prevents successful operation of the network. Moreover, in blind flooding a lot of collisions occur, and they sometimes lead to lost transmissions and prevent the dissemination of information to all the nodes [26].…”
Section: Aodv Performance Problems In Vanetmentioning
confidence: 99%
“…Approximate "tree-ness," which can be formally expressed solely in terms of the metric structure of a space [22], makes the hidden space hyperbolic. 2 …”
Section: A Intuitionmentioning
confidence: 99%
“…It has been shown that many previous routing protocols for MANETs perform poorly in VANETs [6,7] . One of the main problems is that the previous routing protocols fail to achieve This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%